Potential Use of Compounds from Neem Leaves (Azadirachta indica Juss) as PPARg and ERa Inhibitors to Control Breast Cancer Cell Growth In Silico Model - Supriyanto Supriyanto; Muhaimin Rifa'i; Yunianta Yunianta; Simon Bambang Widjanarko (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2020)
Treatment using herbs is currently growing rapidly. Compounds in herbal plants can cure various degenerative diseases. The study aims to analyze the potency of nimbin, deacetylnimbin, salanin, and deacetylsalanin compounds in the neem leaves extract to inhibit target proteins namely PPARg and ERa. PPARg is the main regulator of the function of adipose tissue microvascular endothelial cells (aMVECs) while ERa is a protein that mediates all estrogen effects and it is important in the growth of prostate and breast cancer. Inhibition of ERa can prevent the proliferation and growth of breast cancer cells by affecting the performance of estrogen which binds to hormonal receptors and causes inhibition of breast cancer cell proliferation. The results of in silico analysis show that deacetylnimbin can inhibit ERa protein. The docking analysis shows that deacetylnimbin has the potential to replace tamoxifen as a breast cancer drug. The other studies such in vitro and in vivo are needed to validate in silico study.